The effect of nitrous oxide (entonox) on labour - Naddoni, Devendra B.; Balakundi, Seema K.; Assainar, Kammappa K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Labour pain is one of the most severe types of pain ever to be experienced. The severity of pain during labour is different for each woman. Various pharmacological and non pharmacological methods have been evaluated for their effect on labour pain. Entonox is non-inflammable, tasteless, odorless and colorless gas. This study aims to evaluate the effect of nitrous oxide (entonox) on labour. Methods: This study was conducted on 200 pregnant women with gestational age of 37-41 weeks at New Alma Hospital, Mannarkkad, Kerala, India from March 2015 to July 2015. These patients were randomized to receive either a pre-prepared mixture of 50% nitrous oxide plus 50% oxygen (entonox) (trial) or oxygen (control) groups by a coin. Entonox was started during active phase of labour at the onset of pain in trial group and oxygen was started at 4litres/minute in control group. The patient herself administered entonox connected to the uni-directional valve which enables the women to breathe fresh gas in each inspiration. Parameters such as pain, blood pressure, oxygen saturation, duration of active phase of labour, maternal side effects, Apgar score at 1st and 5th minute were recorded in both the groups. Results: The intensity of labour pain was significantly lower in entonox group (p<0.001) as evident by lower visual analogue scale (VAS) values. There was no difference in blood pressure values in both the groups. The oxygen saturation was higher in control group. The mean duration of active phase of labour in the entonox group was lower compared to the oxygen group. Maternal side effects were significantly higher in entonox group. There were no significant differences in 1st and 5th minute Apgar scores between the two groups. Conclusions: Entonox is cheap, safe and easily available. Though associated with few maternal side effects, it can be quickly and easily used during painful labour. While nitrous oxide analgesia may not be effective for every woman, it is considered a fairly safe and low cost way to manage pain during labour.